HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU DAN KOORDINASI MATA – TANGAN DENGAN HASIL SMASH PADA TIM BOLAVOLI PUTRA SMA NEGERI 1 KERINCI KANAN - Erlan Supranto; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Based on observations made by researchers on the men's volleyball team for male students of SMA Negeri 1 Kerinci Kanan, there are still many players who fail when they do a volleyball smash. The purpose of this study was to determine the relationship between arm and shoulder muscle strength and hand eye coordination with smash accuracy on the men's volleyball team at SMA Negeri 1 Kerinci Kanan. The population that will be used is the men's volleyball team at SMA Negeri 1 Kerinci Kanan consisting of 12 people. The sample in this study was the men's volleyball volleyball team at SMA Negeri 1 Kerinci Kanan as many as 12 people using total sampling technique. The instruments in this study were expandng dynaometer, throw and catch the ball, and the results of the smash. The data obtained were analyzed using multiple correlation. Based on the results of research that the writer has shown that the results obtained by the strength of the arm and shoulder muscles have no relationship with the results of the smash on the Men's Volleyball Team at SMA Negeri 1 Kerinci Kanan. From the results obtained, eye and hand coordination has no relationship with the results of the smash on the Men's Volleyball Team at SMA Negeri 1 Kerinci Kanan. There is no joint relationship between arm and shoulder muscle strength and eye and hand coordination on the results of the smash on the Men's Volleyball Team at SMA Negeri 1 Kerinci Kanan.Key Words: Arm and Shoulder Muscle Strength, Eye and Hand Coordination, Smash Results